2017
DOI: 10.1002/acr.23166
|View full text |Cite
|
Sign up to set email alerts
|

Hip Shape as a Predictor of Osteoarthritis Progression in a Prospective Population Cohort

Abstract: Hip shape is associated with radiographic OA, THR, hip pain, effusion-synovitis, BMLs, muscle strength, and hip structural changes. These data suggest that different shape modes reflect multiple facets of hip OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 30 publications
(63 reference statements)
4
60
0
Order By: Relevance
“…This is both a strength and a weakness of the method. Its strength is that it can detect and isolate coordinated changes so that certain modes become indicative of pathology and can be used as imaging biomarkers . The weakness, demonstrated here, is that the overall difference in shapes between early and late walkers, using all the modes in combination, is subtle, as indicated by the superimposed shapes in Fig .…”
Section: Discussionsupporting
confidence: 88%
“…This is both a strength and a weakness of the method. Its strength is that it can detect and isolate coordinated changes so that certain modes become indicative of pathology and can be used as imaging biomarkers . The weakness, demonstrated here, is that the overall difference in shapes between early and late walkers, using all the modes in combination, is subtle, as indicated by the superimposed shapes in Fig .…”
Section: Discussionsupporting
confidence: 88%
“…Although this represents the first reported GWAS for hip shape, previous candidate gene studies (7,8) have examined associations between OA susceptibility loci and hip shape, following application of SSM to radiographs (Supplemental Transcription factor primarily involved in chondrogenesis, (42) SOX9 activity can be increased through being targeted by PTHLH (33) Campomelic dysplasia, (43) Pierre Robin sequence, (44) Cooks syndrome (45) Chondrodysplasia and abnormal joint formation (46) GSC (14q32.13, rs1243579: upstream)…”
Section: Discussionmentioning
confidence: 99%
“…(16) This implied relationship between hip shape and hip OA is in-keeping with reported associations between hip DXA-derived hip shape, obtained using the same SSM method as used here, and hip OA. (8,9) For example, a wider upper femur as reflected by HSM1, associated with 12p11.22 and 21q22.12 loci related to hip OA, might alter biomechanical forces of the hip and hence risk of hip OA. Femoral head size and shape, related to HSM2 (Supplemental Fig.…”
Section: Astn2mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the influence that Gdf5 and its broad regulatory domains have on hip morphology, in the context of shape parameters relevant to OA, DDH, and dislocation. We revealed that: (1) Gdf5 loss results in substantial dysmorphologies to the proximal femur and acetabulum in line with known features involved in hip instability, developmental dislocation, injury, and adult onset OA; (2) Compared to upstream regulatory sequences, downstream regulatory sequences of Gdf5/GDF5 drive stronger, more ubiquitous prenatal hip expression and uniquely control postnatal hip expression; (3) This regulatory structure is functionally important as downstream sequences were capable of restoring Gdf5 loss-of-function phenotypes to normal, a situation not observed when using the upstream region. These latter two findings have important ramifications to how we understand GDF5 and its association with OA and hip dysplasia/dislocation.…”
Section: Discussionmentioning
confidence: 95%